To evaluate the EASE intervention for reducing anxiety and depression among adolescents in Pakistan: a protocol for a mixed methods study, including a cluster-randomised controlled trial - Fenglin Cao; Lubna Ghazal; Naixue Cui (BMJ Open)
Introduction The rising prevalence of adolescent anxiety and depression in low- and middle-income countries (LMICs) highlights the urgency for effective interventions. Challenges with standard treatments necessitate exploring accessible strategies. In addition, adapting interventions from high-income countries to LMICs raises concerns about efficiency. The LMIC-tailored Early Adolescent Skills for Emotions (EASE) intervention, integrating cognitive-behavioural principles, group sessions, non-specialist delivery and parental involvement, provides a promising solution. This protocol aims to evaluate the effectiveness, acceptability and feasibility of the intervention in public schools in Multan, Pakistan, for addressing anxiety and depression among adolescents.Method and analysis This proposed study aims to achieve its objectives through a two-phase approach by using a mixed methods experimental design. Primarily, a cluster randomised control trial with a two-arm (intervention and waitlist control) single-blinded design will assess the effectiveness of the EASE intervention in reducing anxiety and depression (primary outcome) and parenting, quality of life and psychological distress (secondary outcome) among adolescents aged 13–19, employing a 1:1 allocation ratio. Subsequently, leveraging effectiveness data, the study will explore moderating (eg, socioeconomic characteristics) and mediating pathways (parenting skills and parents’ psychological distress) to enhance our comprehension of the intervention’s effectiveness. Lastly, an exploratory descriptive qualitative study will investigate the perceptions of various stakeholders regarding the acceptability and feasibility of the School-Based Mental Health Programme intervention in the Pakistani context. For the trial data, linear mixed models will be used to account for clustering at the school level and adjust for baseline differences. For the qualitative data, content analysis will be conducted to identify stakeholder perceptions about the intervention.Ethics and dissemination The study received ethical approval from the Ethics Committee of the School of Nursing and Rehabilitation at Shandong University, Jinan, China (Reference No. 2023-R-024) and Institutional Review Board (Ref: IRB-2019/MASH/Approval-06/March/2023) Mukhtar A Sheikh Hospital, Multan. The findings will be shared through publications in peer-reviewed journals and presentations at national and international conferences.Trial registration number This trial is registered at ClinicalTrials.gov (ID NCT06155838).